Conceptualising business risk culture: a study of risk thinking and practice in contemporary dynamic organisations. (15th October 2009) - Kelly, Phil
In response to the challenges regarding the way organisations think individually and collectively about and act upon risk (risk culture) plus recent calls for new approaches to risk management, we investigate risk specialists' current thinking on risk and risk practice. In particular, we seek to review and develop the concept of risk culture in organisations. Organisational risk culture is conceptualised in terms of collective risk thinking to include risk perception and other cognitive processes and risk behaviour. Having conceptualised risk culture, we investigate its determinants and consequences – contingency theory and the concepts of dysfunctional and congruent risk cultures. Drawing on the literature and an empirical study primarily of risk specialists from 100 companies spread over 40 countries, we explore the relationships between organisational cultural variables and review the measurable components of risk culture.